Polyphenol Extracts From Germinated Mung Beans Can Improve Type 2 Diabetes in Mice by Regulating Intestinal Microflora and Inhibiting Inflammation - Shen, Xinting; Jiang, Xiujie; Qian, Lili; Zhang, Aiwu; Zuo, Feng; Zhang, Dongjie (Frontiers in Nutrition, 2022)
Studies have shown that inhibiting inflammation and regulating intestinal microflora imbalance is an significant factor in controlling the development of T2DM.This experiment studied the protective effect of polyphenol extract from germinated mung bean on diabetic C57BL/6 mice.We observed that FBG decreased, glucose tolerance increased, insulin resistance decreased, serum lipid indexes in T2DM mice were improved, and the enzyme activities of ALT and AST in serum were reduced.Meanwhile, the levels of IL-6, TNF-α and CRP in serum decreased, the concentration of IL-10 in serum increased, inhibit the inflammatory reaction induced by diabetes, and repair the morphology of mice liver tissue.At the same time, GMP can regulate the main intestinal flora, Firmicutes, Bacteroidetes and Proteobacteria in diabetic mice, and can also regulate species diversity and improve intestinal flora imbalance.Taken together, our results show that a certain dose of polyphenol extract from germinated mung bean can improve mouse T2DM by inhibiting inflammatory reaction and regulating intestinal microflora.